2021
DOI: 10.1002/jcb.29887
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria are devoid of poly(ADP‐ribose)polymerase‐1, but harbor its product oligo(ADP‐ribose)

Abstract: There are conflicting data about localization of poly(ADP-ribose)polymerase-1 and its product poly(ADP-ribose) in mitochondria. To finally clarify the discussion, we investigated with biochemical and cell biological methods the potential presence of poly(ADP-ribose) polymerase-1 in these organelles. Our data show that endogenous and overexpressed poly(ADP-ribose)polymerase 1 is only localized to the nucleus with a clear exclusion of cytosolic compartments. In addition, highly purified mitochondria devoid of nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
(132 reference statements)
0
5
0
Order By: Relevance
“…A study exploring the localization of PARG in mouse cortical neurons, using the same major experiments for determining subcellular localization, only saw PARP-1 in the nucleus as well [71]. Similar experiments were performed on HeLaS3 and HEK293 cells [72], and also saw no PARP-1 in mitochondria or cytosol, but did observe oligo-ADP-ribose in mitochondria. More recently, it was shown that mitochondrial PARylation did not decrease in U2OS cells treated with inhibitors specific for PARP-1/2, and that U2OS PARP-1 knockout cells showed an increase in mitochondrial PARylation relative to the control [73].…”
Section: The Debate Regarding Mitochondrial Parp-1mentioning
confidence: 78%
“…A study exploring the localization of PARG in mouse cortical neurons, using the same major experiments for determining subcellular localization, only saw PARP-1 in the nucleus as well [71]. Similar experiments were performed on HeLaS3 and HEK293 cells [72], and also saw no PARP-1 in mitochondria or cytosol, but did observe oligo-ADP-ribose in mitochondria. More recently, it was shown that mitochondrial PARylation did not decrease in U2OS cells treated with inhibitors specific for PARP-1/2, and that U2OS PARP-1 knockout cells showed an increase in mitochondrial PARylation relative to the control [73].…”
Section: The Debate Regarding Mitochondrial Parp-1mentioning
confidence: 78%
“…However, there has been a lack of direct evidence, which has led to much skepticism about mtPARP1. Some studies claim that mitochondria are completely devoid of PARP1, that PARylated proteins enter mitochondria 52 or that mitochondria harbor enzymes other than PARP1 with ADP-ribosyltransferase activity 11 . On the other hand, some studies report the involvement of PARP1 in mtDNA metabolism, demonstrating direct interactions between PARP1 and mtDNA for mtDNA maintenance 9 and repair 53 .…”
Section: Discussionmentioning
confidence: 99%
“…170). Importantly, the pathways stemming from oxidative stress-induced PARP2 activation were identified in plants ( Refs 184,185) 197). PARP2 impacts on lipid metabolism in the white adipose tissue (Ref.…”
Section: Parp2 In Oxidative Stressmentioning
confidence: 99%
“…Interestingly, in Arabidopsis PARP2 is present in the mitochondria (Ref. 196) that is an interesting phenomenon, as in mammalian cells no PARylating activity was identified in the mitochondria (Refs 165, 197).…”
Section: Parp2 In Metabolic Regulationmentioning
confidence: 99%
See 1 more Smart Citation